The concept of bio-economic mulching in droughty tropical agroecosystems and its trans-season effects on soil hydro-thermal regime and okra performance - Benedict Odinaka Okorie; Justina O. Obi; Geraldine U. Chioke; Sunday E. Obalum; Chinaza J. Onah; Adaobi L. Nnadi; Charles A. Igwe; Martin E. Obi (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Mulching is an effective soil-water conservation technique in high-evaporative-demand tropical climates. Because of the drawbacks in bulk application of organic mulches, we introduce the concept of bio-economic mulching (BEM), a one-time low-rate application of organic mulch to improve soil productivity while sustaining economic viability. The study evaluated the effects of BEM (dry-grass mulching at 0, 2, 4, and 6 t ha–1) on soil hydrothermal properties of sandy-loam Ultisols using okra growth during 4–9 weeks after sowing in successive rainy-to-dry/partially rainfed season (PRS) and rainy/completely rainfed season (CRS). During the PRS, soil volumetric moisture content (q) increased (10.02%–25.50%), but soil temperature decreased (37.67–26.67°C) as BEM rate increased. A similar q trend (8.71%–18.37%) occurred during the CRS. Soil thermal conductivity (0.78to 4.88 W m–1 K–1), thermal diffusivity (3.95 × 10–7 to 35.97 × 10–7 m2 s–1), and heat flux (15.00 to 85.56 W m–2) generally decreased as q increased with BEM application rate particularly during the PRS; the reverse prevailed for volumetric heat capacity (1.33 × 106 to 2.25 × 106 J m–3 K–1). Okra plant height differed (BEM-6 > BEM-4 > BEM-2/BEM-0) in the PRS, but BEM-6 and BEM-4 gave the tallest and shortest plants, respectively in the CRS. Fruit yield was 1.8- and 9.5-fold higher in BEM-6 than BEM-4 in PRS and CRS, respectively. Mulch treatment-induced temporal variations in soil q influenced okra performance indices of plant height (r2 = 0.85) and total fresh fruit yield (r2 = 0.69). In droughty tropical environments, BEM implementation at 6 t ha−1 could engender soil hydrothermal regime favoring vegetable production beyond the ‘drier’ first season and even more pronouncedly in the second season.